Adaptive nonlinear control of the DC‐DC buck converters operating in CCM and DCM. (23rd August 2012) - Salimi, Mahdi; Soltani, Jafar; Markadeh, Gholamreza Arab; Abjadi, Navid Reza
SUMMARY In this paper, an adaptive nonlinear controller is designed for regulating the output voltage of DC‐DC buck converters, which is stable and robust with subject to widely changes of load demands and input voltage variations. The proposed controller is developed based on adaptive backstepping approach and can be applied for both Continuous and Discontinuous Conduction Modes (CCM and DCM). Using a stand‐alone TMS320F2810 digital signal processor from Texas instruments, some simulations and experimental results have been obtained to verify the proposed control approach. These results are in good agreement and prove the effectiveness and capability of the controller for both CCM and DCM operations. Copyright © 2012 John Wiley & Sons, Ltd.